High content screening assay for identifying inhibitors against active and dormant state intracellular Mycobacterium tuberculosis - Yeware, Amar; Agrawal, Sonia; Sarkar, Dhiman (Journal of Microbiological Methods, 2019)
The antitubercular drug development pipeline could start with an in vitro investigation of several compounds to examine their effect on active and dormant state Mycobacterium tuberculosis (Mtb). However, in vitro screening of dormant state bacilli cannot provide enough information on the simultaneous effect of a compound on the host. Therefore, we developed a live cell fluorescence based screening protocol by utilizing the high content system for determining the effect of inhibitors against active and dormant state intracellular mycobacteria. THP-1 macrophages infected with an actively growing and hypoxia derived dormant Mtb culture were standardized to develop the screening protocol. The signal to noise ratio and the Z' factor of this assay were found to be 7.5-29 and 0.6-0.8, respectively, which confirm the robustness of the protocol. The protocol was then validated with standard inhibitors. This newly developed drug screening assay offers an easy, safe, image based high content screening tool to search for novel antitubercular inhibitors against both active and dormant state intracellular mycobacteria. Therefore, this assay could fill in the gap between in vitro and in vivo latent tuberculosis drug screening programs.